A comprehensive model for uniform heat flux inside cavity receiver with air-carbon mixture. (December 2017) - Jin, Yabin; Fang, Jiabin; Wei, Jinjia; Wang, Xinhe
Abstract: Cavity receiver is one of the main components of efficient concentrating solar collector systems. It has the ability to operate at relatively higher temperature and efficiency. The safety and thermal efficiency of solar cavity receiver can affect the efficiency of the whole power system. However, the non-uniform distribution of heat flux and temperature inside the cavity tends to cause the operation instability and bring damage to the tube as well. In the present work, a comprehensive numerical model was developed by coupling Monte Carlo Ray Tracing (MCRT) and Finite Volume Method (FVM) to simulate the thermal performance of a 2D square solar cavity filled with air-carbon particle mixture. Firstly, the complicated photon transmission in the air-carbon particle mixture absorber is simplified as the transmission process in the statistically homogenous and isotropic turbid media. The solar heat flux distribution from the aperture to the wall is simulated by MCRT, and the photo-thermal convection process in the cavity receiver is modeled by FVM. Then the two parts are coupled in the cavity receiver by transferring the absorbed energy computed by MCRT to FVM, and this energy is applied as a source term of the energy equation in the FVM part. Based on this model, the temperature and heat flux characteristics of the cavity receiver were studied at various carbon densities. The result indicated that the air-carbon particle mixture can actively take part in the radiation and it appears that it has a remarkable effect on the temperature homogenization. It decreases the temperature of wall 3 dramatically and increases the temperature of wall 2 and wall 4. The relationships between the temperature unevenness and the number particle density were also analyzed. The temperature unevenness on the wall 3 drops most with the increase of number density of carbon particle, from 25.0K to 2.4K. The unevenness of temperature on the top and bottom walls also decreases slightly by 3K. In addition, the present model is proved to be accurate and reliable for studying the complex energy convection process in the cavity filled with air-carbon particle mixture. The result of the cavity receiver study can also provide a method to effectively improve the uniformity of the heat flux distribution on the wall.